2021
DOI: 10.1111/cen.14460
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and outcomes of adrenal ganglioneuromas: A cohort study and a systematic review of literature

Abstract: Objective To describe the presentation and outcomes of patients with adrenal ganglioneuromas (AGNs). Design Single‐centre retrospective cohort study (1 January 1995 to 31 December 2019) and systematic review of literature (1 January 1980 to 19 November 2019). Patients Diagnosed with histologically confirmed AGN. Measurements Baseline clinical, imaging and biochemical characteristics, recurrence rates and mortality. Subgroup analysis was performed on tumours with histologic elements of ganglioneuroma and pheoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
2
11
1
Order By: Relevance
“…An AGN as demonstrated on a CT scan is homogenous and of low attenuation in the precontrast phase, mild attenuation in the postcontrast phase, and sometimes either homogenous or heterogeneous in appearance in the ate phase [ 3 11 ]. This pattern was repeatedly observed by us as well as by others [ 4 5 6 8 9 12 ]. Calcification is another indication for AGN seen on CT; however, its prevalence widely varies between studies from 11.1% [ 2 ] to as high as 82.4% [ 3 ].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…An AGN as demonstrated on a CT scan is homogenous and of low attenuation in the precontrast phase, mild attenuation in the postcontrast phase, and sometimes either homogenous or heterogeneous in appearance in the ate phase [ 3 11 ]. This pattern was repeatedly observed by us as well as by others [ 4 5 6 8 9 12 ]. Calcification is another indication for AGN seen on CT; however, its prevalence widely varies between studies from 11.1% [ 2 ] to as high as 82.4% [ 3 ].…”
Section: Discussionsupporting
confidence: 84%
“…A male-to-female ratio of 2:1 has been reported for adrenomedullary tumors [ 15 ]; however, an equal ratio for both sexes has been found in the present study as well as in other studies [ 9 14 ]. AGN has been reported to accompany hereditary familial syndromes, such as NF1 and NF2 [ 1 2 14 ], and 1 study also reported a single AGN case with an associated multiple endocrine neoplasia 2 syndrome [ 8 ].…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations